Investor-state dispute settlement and international investment agreements : the case of the Gulf Cooperation Council member states - Price, David S. (Lawyer); Hallam, Amelia; Naim, Nadia (Routledge, 2024)
"This book examines the international investment agreements and the dispute settlement mechanisms contained therein which bind the Gulf Cooperation Council member states. The Gulf Cooperation Council (GCC), comprising Bahrain, Kuwait, Oman, Qatar Saudi Arabia, and the United Arab Emirates, is complex and unique. Recently, all member states have experienced increasing investor-state arbitration claims, while their nationals are increasingly instituting investor-state arbitrations to protect their own foreign investments. Intra-GCC disputes, though relatively rare, have also appeared, largely as a result of the recent Gulf crisis. While focusing particularly upon the Investor State Dispute Settlement experience of member states as respondents, the book also explores the experiences of their nationals as claimants to determine how they can approach Investor State Dispute Settlement in future. The book also reflects on existing treaty making practices, making recommendations for regional level dispute settlement to improve upon Investor State Dispute Settlement outcomes. This book provides a detailed analysis of the global investor-state dispute settlement regime and international investment agreements, and will be of interest to students, academics and practitioners with an interest in international investment law and arbitration"-- Provided by publisher.
Keywords: Gulf Cooperation Council.; Arbitration agreements, Commercial -- Persian Gulf States.; Arbitration and award -- Persian Gulf States.; International commercial arbitration -- Persian Gulf States.; Investments, Foreign -- Law and legislation -- Persian Gulf States.; Dispute resolution (Law) -- Persian Gulf States.; Investments, Foreign (International law); elektronické knihy; electronic books